2020
DOI: 10.1186/s12969-020-00476-z
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine in pediatric rheumatology: this is the time for the community to embrace a new way of clinical practice

Abstract: Background The use of telemedicine in pediatric rheumatology has been historically low. The current COVID 19 global pandemic has forced a paradigm shift with many centers rapidly adopting virtual visits to conduct care resulting in rapid expansion of use of telemedicine amongst practices. Body This commentary discusses practical tips for physicians including guidance around administrative and governance issues, preparation for telemedicine, involving the multidisciplinary care team, and teaching consideratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…Similarly, a study of adult and pediatric patients from a single center in New York City early in the pandemic found that 40% of patients reported experiencing a flare in the prior month and that patients reported experiencing anxiety when coming in for routine or urgent visits regarding their rheumatic conditions (46). New guidance has been provided to improve telemedicine assessments, including standardizing the musculoskeletal physical exam using the video version of pGALS, V‐pGALS (47). With rapidly improving technology, the use of telemedicine will likely persist beyond the pandemic to maintain full access to clinical care.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a study of adult and pediatric patients from a single center in New York City early in the pandemic found that 40% of patients reported experiencing a flare in the prior month and that patients reported experiencing anxiety when coming in for routine or urgent visits regarding their rheumatic conditions (46). New guidance has been provided to improve telemedicine assessments, including standardizing the musculoskeletal physical exam using the video version of pGALS, V‐pGALS (47). With rapidly improving technology, the use of telemedicine will likely persist beyond the pandemic to maintain full access to clinical care.…”
Section: Resultsmentioning
confidence: 99%
“…The instrument also may not be able to identify small effusions or detect active joints in young children when used over telemedicine. Recently, Shenoi et al ( 30 ) proposed the Video-pGALS (an adapted version of the pGALS), but this has not been validated and was created using input from a small group of pediatric rheumatologists. Additional research needs to be undertaken to determine whether this tool can accurately assess joint disease activity in a virtual setting.…”
Section: Discussionmentioning
confidence: 99%
“…Telemedicine offers a plausible solution [ 32 ]. Recently, there has been increased access to and reliance on remote meeting systems [ 33 ]. Tele-consults through platforms such as zoom can be used to enhance multi-disciplinary care for patients.…”
Section: The Current State Of Pediatric Rheumatology In Africamentioning
confidence: 99%
“…Further research is required to explore how best to utilize telemedicine to promote pediatric rheumatology in Africa. In solidarity with global partners, researchers from Africa are participating in the validation of the virtual pediatric gait, arms, leg, spine (PGALS) screening examination as part of a global telemedicine initiative [ 33 ]. More research is needed to explore the feasibility of telemedicine for pediatric rheumatology in Africa.…”
Section: The Current State Of Pediatric Rheumatology In Africamentioning
confidence: 99%